RDA description of electronic and digital resources in the digital library - García, Ariel Alejandro Rodríguez; Monroy - Muñoz, Adriana (Qualitative and Quantitative Methods in Libraries, 2017)
This work focuses on examining the electronic resources description, particularly the RDA description that needs to be added to the digital library. The research stresses the organization of information pertaining to resources with digital features by using RDA: Resources Description & Access (RDA 2011). We add to this, the recording attributes to access the digital collection. Taking into account the theoretical principles underlying the current schemes to describe the information resources, we contrast them with the model that governs RDA for the description of the access points and the recording attributes of works, expressions, manifestations and items. The model of representation and description of the electronic resource is exemplified by digital photography while identifying the attributes of electronic resources and digital photography that will be necessary for the discovery of the resource in the digital medium.